2016
DOI: 10.1111/ppl.12525
|View full text |Cite
|
Sign up to set email alerts
|

A novel root‐to‐shoot stomatal response to very high CO2 levels in the soil: electrical, hydraulic and biochemical signalling

Abstract: Investigations were undertaken in the context of the potential environmental impact of carbon capture and storage (CCS) transportation in the form of a hypothetical leak of extreme levels of CO2 into the soil environment and subsequent effects on plant physiology. Laboratory studies using purpose built soil chambers, separating and isolating the soil and aerial environments, were used to introduce high levels of CO2 gas exclusively into the rhizosphere. CO2 concentrations greater than 32% in the isolated soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…This response was investigated in more detail and found to be a whole plant response affecting the water status of the plant. 27 The majority of the findings of this short-term study (a reduction in above and below ground biomass when CO 2 treatments are compared to controls) reflect those conducted on more long-term field trials such as work at the Zero Emission Research and Technology (ZERT) Center, Montana, USA 2 and the ASGARD facility. [23][24][25]…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This response was investigated in more detail and found to be a whole plant response affecting the water status of the plant. 27 The majority of the findings of this short-term study (a reduction in above and below ground biomass when CO 2 treatments are compared to controls) reflect those conducted on more long-term field trials such as work at the Zero Emission Research and Technology (ZERT) Center, Montana, USA 2 and the ASGARD facility. [23][24][25]…”
Section: Resultsmentioning
confidence: 79%
“…The reduction in root biomass provides a mechanism for the inability of plants to access sufficient nutrients and water. This response was investigated in more detail and found to be a whole plant response affecting the water status of the plant …”
Section: Resultsmentioning
confidence: 99%
“…The content of leaf water and root TP in the ‘CO 2 ’ treatment condition was significantly decreased by 3% and 27% compared to the control, respectively (Table ). These results indicated that root absorption of soil water and nutrients was lower in the ‘CO 2 ’ treatment condition, which might lead to changes in the rhizospheric conditions . Meanwhile, the roots in the ‘CO 2 treatment condition’ had 73% and 7% higher starch and TC content compared to the control, respectively (Table ).…”
Section: Resultsmentioning
confidence: 92%
“…Standard errors are shown as perpendicular lines (n = 6) and asterisks represent significant differences between the 'CON' and 'CO 2 ' treatments according to ANOVA as follows: ***, P < 0.01; **, P < 0.05; and *, P < 0.10. the rhizospheric conditions. 20,22,30 Meanwhile, the roots in the 'CO 2 treatment condition' had 73% and 7% higher starch and TC content compared to the control, respectively ( Table 3). As storage organs, roots can store photosynthate in the form of starch.…”
Section: Plant and Soil Responsesmentioning
confidence: 99%
See 1 more Smart Citation